The Relationship of Various Risk Factors with LBW in South Tangerang City General Hospital for the Period March-October 2021 - Sharon Levita; Louisa Langi (Faculty of Medicine Universitas Kristen Duta Wacana, 2022)
Background Low birth weight (LBW) is a serious child health problem that requires global attention, especially in developing countries or with low economic status. Indonesia itself is in the ninth position of the country with the highest prevalence of LBW in the world. Therefore, it is important to examine various factors that can increase the risk of LBW, and it is hoped that it can prevent the occurrence of LBW, considering the complications that LBW can experience in both the short and long term.Objectives This study aims to determine the relationship between various risk factors and LBW in South Tangerang City General Hospital for the period March-October 2021.Methods This study is an analytical observational study using the cross-sectional method. Sources of data were obtained from medical records and books on Maternal and Child Health (KIA) of respondents, with the criteria of respondents being mothers with a history of giving birth to low birth weight (<2500 g), having an active cell phone number and recorded in the NICU registration at South Tangerang City General Hospital, and still having Maternal and Child Health (KIA) book.Results There was a significant relationship between risk factors for gestational age (p=0.046) and frequency of ANC visits (p=0.035) with low birth weight, but there was no significant relationship between risk factors for maternal age (p=0.193), maternal education (p=0.087), maternal occupation (p = 0.618), and family income (p = 0.320) with low birth weight in South Tangerang City General Hospital for the period March-October 2021.Conclusion Gestational age and frequency of ANC visits are statistically significant risk factors for LBW incidence in South Tangerang City. Maternal age, maternal education, mother's occupation, and family income are not statistically associated with low birth weight in South Tangerang City General Hospital